Análisis comparativo de la composición de las exportaciones de Loreto en el periodo pre y post pandemia 2018 - 2021 - Vasquez Salinas, Jimmy Gonzalo Allison (2022)
The COVID 19 pandemic came to affect not only the health of the population, but also economic activities, clearly differentiating the pre-pandemic period from the post-pandemic period. The objective of this research is to carry out a comparative analysis of the composition of Loreto's exports in the pre- and post-pandemic period 2018 - 2021. Taking this objective into account, this Quantitative type study is carried out, Descriptive level and non-experimental design. The research concludes that there are no changes in the composition of exports in terms of the three most important products, but there are from fourth place both in the pre- and post-pandemic period. In both periods Crude Oil is the main exported product. The main export products in the pre-pandemic period are: Fuels (87.23%), Wood (4.30%) and Ornamental Fish (3.14%); but, in the post-pandemic period, Agro and Agroindustry products (5.95%) have displaced Ornamental Fish (5.10%), demonstrating that in the post-pandemic period, food consumption is prioritized, not buying non-basic products. Chile is the main destination country for Loreto's exports. The main fuel exporting company was Pacific Stratus Energy del Perú S.A. (56.94%); while for wood it is Inversiones La Oroza SRL. (1.94%); and Acuatrade SAC. (1.70%) from Fishing.